Pengaruh Pengeluaran Pemerintah, Ekspor, Infrastruktur Jalan dan Jumlah Penduduk Terhadap Pendapatan Nasional Indonesia - Muhammad Nasir; Diana Sari (Syiah Kuala University, 2015)
This paper aims to identify and analyze the effect of government spending, exports, road infrastructure and population on national income. The data used are secondary data and using time series data for the period 1995 to 2012 taken from various relevant agencies. The analytical method used is quantitative descriptive method using multiple linear regression analysis model. Based on the findings, the government spending, exports, road infrastructure and population positively effect on Indonesia's national income. Therefore, it can be recommended to the Government of Indonesia in order to increase government spending, exports, and expanding the road infrastructure across Indonesia.